Harvard business review : interviews with CEOs (Harvard Business School P. BostonUS, 2000)
Captures the business thinking of 8 Chief Executive Officers on topics including: driving change; organizing for empowerment; unleashing the power of learning; competing on customer service; and governing the family-owned enterprise.
Located in the Learning Resource Centre